Measurement of sin2?lepteff using e+e? pairs from ??/Z bosons produced in p¯p collisions at a center-of-momentum energy of 1.96 TeV - Aaltonen, T.; Amerio, S.; Amidei, D.; Anastassov, A.; Annovi, A.; Antos, J.; Apollinari, G.; Appel, J. A.; Arisawa, T.; Artikov, A.; Asaadi, J.; Ashmanskas, W.; et al. (My University, 2016)
At the Fermilab Tevatron proton-antiproton (pp) collider, Drell-Yan lepton pairs are produced in the process pp?e+e-+X through an intermediate ??/Z boson. The forward-backward asymmetry in the polar-angle distribution of the e- as a function of the e+e - pair mass is used to obtain sin2?efflept, the effective leptonic determination of the electroweak-mixing parameter sin2?W. The measurement sample, recorded by the Collider Detector at Fermilab (CDF), corresponds to 9.4 fb-1 of integrated luminosity from pp collisions at a center-of-momentum energy of 1.96 TeV, and is the full CDF Run II data set. The value of sin2?efflept is found to be 0.23248±0.00053. The combination with the previous CDF measurement based on ?+?- pairs yields sin2?efflept=0.23221±0.00046. This result, when interpreted within the specified context of the standard model assuming sin2?W=1-MW2/MZ2 and that the W- and Z-boson masses are on-shell, yields sin2?W=0.22400±0.00045, or equivalently a W-boson mass of 80.328±0.024 GeV/c2. © 2016 American Physical Society.
Citation: Aaltonen, T., Amerio, S., Amidei, D., Anastassov, A., Annovi, A., Antos, J., . . . Zucchelli, S. (2016). Measurement of sin2 ?eff lept using e+e- pairs from ??/Z bosons produced in pp collisions at a center-of-momentum energy of 1.96 TeV. Physical Review D - Particles, Fields, Gravitation and Cosmology, 93(11). doi:10.1103/PhysRevD.93.112016